2011
DOI: 10.3389/fmicb.2011.00118
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Diversity of Pseudomonas aeruginosa Lipopolysaccharide

Abstract: Lipopolysccharide (LPS) is an integral component of the Pseudomonas aeruginosa cell envelope, occupying the outer leaflet of the outer membrane in this Gram-negative opportunistic pathogen. It is important for bacterium–host interactions and has been shown to be a major virulence factor for this organism. Structurally, P. aeruginosa LPS is composed of three domains, namely, lipid A, core oligosaccharide, and the distal O antigen (O-Ag). Most P. aeruginosa strains produce two distinct forms of O-Ag, one a homop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
280
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 226 publications
(306 citation statements)
references
References 172 publications
9
280
0
5
Order By: Relevance
“…Mutations in the gene cluster regulating the production of alginate were selected by Ab09, and could reduce the efficiency of infection of all the phages. The wzy, wzz2 and wbpL genes are members of the heteropolymeric O-specific antigen biosynthesis cluster in PAO1 (Lam et al, 2011). Gene migA encodes a rhamnosyltransferase involved in LPS core capping (Poon et al, 2008), whereas wapH and dnpA are known to be involved in the synthesis of LPS (Hansen et al, 2007;Liebens et al, 2014), and pgi encodes a glycosyltransferase (Rocchetta et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the gene cluster regulating the production of alginate were selected by Ab09, and could reduce the efficiency of infection of all the phages. The wzy, wzz2 and wbpL genes are members of the heteropolymeric O-specific antigen biosynthesis cluster in PAO1 (Lam et al, 2011). Gene migA encodes a rhamnosyltransferase involved in LPS core capping (Poon et al, 2008), whereas wapH and dnpA are known to be involved in the synthesis of LPS (Hansen et al, 2007;Liebens et al, 2014), and pgi encodes a glycosyltransferase (Rocchetta et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous mutations responsible for phage resistance are frequently related to alterations in the phage receptor (Hyman & Abedon, 2010;Labrie et al, 2010). In P. aeruginosa, adsorption mutants are principally affected in type IV pili, often used as receptors by podoviruses (Chibeu et al, 2009) and siphoviruses, or in LPS, a major virulence factor (King et al, 2009;Lam et al, 2011) involved in the binding of myoviruses. We and others showed that large chromosomal deletions could be selected in bacteria resistant to single or multiple phages.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa is well known for its ability to cause chronic and extensively drug-resistant infections (1). The outer membrane lipopolysaccharide (LPS) layer is a major virulence factor of P. aeruginosa (2). LPS has been linked to antibiotic resistance and immune evasion.…”
mentioning
confidence: 99%
“…LPS has been linked to antibiotic resistance and immune evasion. Furthermore, LPS is one of the receptors that determines the susceptibility of the bacterium to bacteriophages and pyocins (2)(3)(4). Our ability to control P. aeruginosa infections depends on the availability of accurate typing methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation